From peaks to ports: Insights into tin provenance, production, and distribution from adapted applications of lead isotopic analysis of the Uluburun tin ingots. (October 2021) - Powell, Wayne; Johnson, Michael; Pulak, Cemal; Yener, K. Aslihan; Mathur, Ryan; Bankoff, H. Arthur; Godfrey, Linda; Price, Michael; Galili, Ehud
Abstract: Lead isotope analysis (LIA) can be applied to tin provenance studies when both the U–Th–Pb characteristics of cassiterite and potential Pb contamination are taken into account. As cassiterite (SnO2 ) contains higher concentrations of U than Pb and negligible Th, radioactive decay increases 206 Pb/ 204 Pb and 207 Pb/ 204 Pb ratios in cassiterite over time. However, 208 Pb/ 204 Pb ratio retains its primary value and can be correlated with LIA databases. A majority of documented Bronze Age tin ingots from Europe have Pb in excess of the 5 ppm maximum that can be derived from Cenozoic to Late Paleozoic cassiterite. A minute mass of galena (PbS) in the ore concentrate is sufficient to mask the cassiterite-derived lead, as would the addition of any lead contaminant introduced in the smelting/casting process. If the galena is cogenetic with the cassiterite, then LIA will be unaffected. The inclusion of uranium-rich minerals in the tin ore concentrate is another potential source of excess lead. In this case, the additional Pb is uranogenic, and so 206 Pb/ 204 Pb and 207 Pb/ 204 Pb will reflect the age of the uranium minerals, but 208 Pb/ 204 Pb will retain its primary value. If the U-minerals are cogenetic or coeval with tin mineralization, then a Pb isochron age will indicate the age of the ore. Between 1984 and 1994, at least 117 ingots, or roughly one tonne, of tin was raised from the Late Bronze Age Uluburun shipwreck (ca. 1320 B.C.). Over half of the analyzed ingots from this wreck site have high Pb concentrations (>100 ppm), indicative of contamination from non-radiogenic lead associated with lead metal or galena. LIA indicates that the Pb originated from the Pb–Ag-rich Bolkardağ region of the south-central Taurus Mountains. A second group of approximately 28 tin ingots with lower Pb content (<100 ppm) contain additional uranogenic Pb but retain 208 Pb/ 204 Pb compositions that overlap with the ca. 300 Ma tin regions of Western Europe and Central Asia, with the most likely source being the Tienshan Mountains in Kyrgyzstan, Tajikistan, and Uzbekistan. By compensating for previous uncertainty around the use of Pb isotopes for sourcing tin objects, it is now possible to contextualize the Uluburun tin ingots more securely within the metallurgical systems of the Central Taurus-Cilicia-Amanus axis. Recent scholarship has shown that tin production in the South-Central Taurus region had taken place at a scale not previously anticipated. Two parallel production systems appear to have been in place serving elite and common consumption networks via markedly different technologies. The South-Central Taurus and Cilician cities served as important components of maritime and terrestrial metal distribution around the eastern Mediterranean, providing a range of metals from a single geographical region. Graphical abstract: Image 1 Highlights: 206 Pb and 207 Pb in most tin ingots represent a mixture of primary and radiogenic Pb. 208 Pb in tin objects is primary and 208 Pb/ 204 Pb can compared with sulfide ores. Most tin ingots in Uluburun shipwreck were derived from the Taurus Mountains. Two parallel production systems in place for LBA tin. South-Central Taurus and Cilicia served as important components of LBA metal trade.